3 + 4abs(x/2 + 3) = 11 Subtract 3
4 abs(x/2 + 3) = 11 - 3
4 abs(x/2 + 3) = 8 Divide by 4
abs(x/2 + 3) = 8/4
abs(x/2 + 3) = 2
Solution 1
x/2 + 3 = 2 Subtract 3
x/2 = 2 - 3
x/2 = - 1 Multiply by 2
x/2 *2 = - 2
x = - 2
Solution 2
x/2 + 3 = - 2
x/2 = - 2 - 3
x/2 = - 5 Multiply by 2
x = -5 * 2
x = -10
Solutions
x = - 2 <<<< answer 1
x = -10 <<<< answer 2
Answer:
123456789101112131415161718192021222324252627282930
Step-by-step explanation:
hahaha
Answer: y =
Step-by-step explanation: look for the lcm
a=
cross multiply
ax =9xy + 2
ax - 2 = 9xy
divide both sides by 9x
y=
Answer:
Sometimes
Step-by-step explanation:
Lets see
Let x be a positive number
x=3
|3| = 3
True
Let x =0
|0| = 0
True
Let x be a negative number
x=-3
|-3| =-3
3 = -3
False
So this is sometimes true
Answer: -95/42 for exact
-2 11/42 for mixed
Step-by-step explanation: